Gender as a moderator in the relationship between interest in learning religion and religious discipline toward pesantren regulations - Fitriani, Yulia; Amilda; Sari, Wina Diana; Yulia Fitriani (Psikis : Jurnal Psikologi Islami, 2025)
This study aimed to analyze the relationship between religious learning interest and religious discipline of Islamic boarding school students in obeying Islamic boarding school regulations, by including gender as a moderator variable. A total of 127 Islamic boarding school students were selected through cluster random sampling technique. Data collection was conducted using two psychological instruments. Religious learning interest was measured using the Attitudes Toward Religion Scale (Wang et al., 2019) which consists of 10 items with two factors, namely Interest and Position, and has a Cronbach's alpha reliability between 0.75 and 0.85. Religious discipline was measured using the Measure of Islamic Religiousness (Raiya et al., 2018) which consists of 60 items on seven subscales covering three dimensions, with a Cronbach's alpha value above 0.70 indicating strong internal consistency. Moderated Regression Analysis (MRA) showed that interest in religious learning significantly influenced religious discipline (β = 0.68, p < 0.001), and gender moderated the relationship (ΔR² = 0.04, p < 0.05). The effect of this relationship was stronger for female students, indicating that they tend to have higher levels of religious discipline when their interest in religious learning is also high. MANOVA results confirmed a significant effect on seven discipline subscales, especially on prayer discipline and participation in Islamic boarding school activities (p < 0.001). These findings implied that pesantren-based educational strategies should consider gender-responsive approaches to foster religious discipline, particularly by enhancing learning interest through tailored pedagogical and mentoring methods.